Prediction Of Blast-Induced Ground Vibration During Blasting At Batu Tiga Quarry Masai - Khalid, Akmal Hakim (Universiti Sains Malaysia, 2017)
The study of analysing the ground vibration due to blasting was conducted in order to analyse ground vibration during blasting at BTQ Masai, Johor, Malaysia. The complaints of following blasting are usually caused by an excess of noise, airblast, ground vibration. The main objectives of this study were to study about the ground vibration and its relationship with scaled distance and minimize the environmental effect. The seismograph monitoring device was employed to determine the vibration reading during the blasting activity and also the air blast level. Laboratory work such as Point Load Test was performed in accordance (ASTM D5731 – 08, 1995) to obtain the relevant parameters. Through this study, there will be an understanding on the scaled distance affecting the vibration reading, determination of site constant and prediction of 95% confidence level. Results show that there is significant factor between the distances from monitoring device to the blasting area and maximum instantaneous charge (MIC).